Nimbus: повесть о докторе Гаазе / Александр Нежный - Нежный Александр Иосифович (Соль земли)
Экземпляры: ф.11 (20140903) / Инвентарный номер: 058875 / Цена: 220.00 / Авт.знак: Н 43 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6